Bibliometric analysis of ferroptosis: a comprehensive evaluation of its contribution to lung cancer - Yao, Feifei; Guo, Feng; Sun, Chuanzhong; Wang, Erdong; Wang, Hang; Li, Na (Frontiers in Genetics, 2025)
ObjectivesThis study employs bibliometric analysis to track evolution and identify trends of key topics in ferroptosis within the context of lung cancer. By identifying emerging research areas, our aim is to provide valuable insights and directions for researchers in this field.MethodsRelevant papers and reviews on ferroptosis in lung cancer were retrieved from the Web of Science Core Collection database on 5 February 2024. Bibliometric analysis was conducted using CiteSpace 6.2.R3, VOSviewer 1.6.20, R 4.3.0, Bibliometric and Microsoft Excel 2019.ResultsFrom 2015 to 2020, publications related to ferroptosis in lung cancer were sparse but showed a steady increase. Post-2020, there has been a significant surge, with a 6.4-fold increase observed by 2023. Overall, authors from 4,033 institutions across 42 countries/regions contributed 606 papers published in 262 academic journals. China emerged as the leading contributor, while the United States maintained dominance. Lifang Ma was the most prolific author, with DIXON SJ, YANG WS, and STOCKWELL BR being the most frequently co-cited. Effective communication and collaboration among scholars are lacking. Key journals include Frontiers in Pharmacology for publication output, and Nature and Cell for citation frequency. Research focuses on molecular mechanisms of ferroptosis, including endoplasmic reticulum stress, tumor microenvironment, and autophagy. Therapeutic targets like GPX4, SLC7A11, P53, FSP1, Nrf2, LSH, STYK1/NOK, and ACSL4 are prominent. Traditional Chinese medicine also shows clinical value in ferroptosis research.ConclusionFerroptosis, as a promising research avenue with significant clinical applications in lung cancer, continues to undergo rapid development. The study of iron death in lung cancer will remain a critical research focus in the future.